2016
DOI: 10.32007/med.1936/jfacmedbagdad.v58i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Asthma Control Test (ACT) with (GINA) guidelines in the Assessment of Asthma Control and determine if can use Asthmda Control Test ACT as alternative to Gina guidelines in control asthma.

Abstract: Background: The gold standard in assessing asthma control is the Global Initiative for Asthma (GINA) criteria. And because of the difficulties of access to pulmonary functions tests, The ACT has the added advantage that it does not require lung function assessment. Objectives: The aim of this study is to assess asthma control through ACT score and GINA guideline, and to determine if the ACT can be as useful as the GINA-guidelines criteria in assessing asthma control in Iraq. Patient and method: Cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Nowadays, despite many advances in asthma diagnosis and treatment, the prevalence of controlled asthma is still low worldwide, including in Iraq [9]. It is reported that the level of asthma control among adult is still less than expected, that is, in Baghdad, was (5%) only [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, despite many advances in asthma diagnosis and treatment, the prevalence of controlled asthma is still low worldwide, including in Iraq [9]. It is reported that the level of asthma control among adult is still less than expected, that is, in Baghdad, was (5%) only [10].…”
Section: Introductionmentioning
confidence: 99%